Parent-to-Progeny Transfer and Recombination of T4rII Bacteriophage - Carlson, Karin (1970)
Transfer of parental, light (not substituted with 5-bromodeoxyuridine) (32)P-deoxyribonucleic acid (DNA) from rII(−) mutants of T4 bacteriophage to heavy (5-bromodeoxyuridine-substituted) progeny in Escherichia coli B was less homogeneous than in wild phages. The net transfer was 5 to 20% of the value for wild T4 phage, and the parental contribution per progeny DNA molecule amounted to 7 to 100% of the genome. Three classes could be distinguished, based on the density distribution of parental label in CsCl analysis of the progeny phages. “Far recombined” phages contain parental material only in semiconservatively replicated subunits covalently attached to progeny DNA, amounting to 5 to 10% parental contribution per genome. “Intermediate recombinants” contain, aside from conventional recombinant DNA, parental DNA banding at the original, light density. This DNA may be unattached to heavy progeny DNA or attached by weak bonds which are very sensitive to shearing during the extraction procedure. The parental contribution is 10 to 50% per progeny DNA molecule in this class. “Conservative” phages band close to the parental, light density in CsCl; their DNA is purely light. When the parental phage is labeled with both (3)H-leucine (capsid) and (32)P (DNA), the specific activity of (3)H/(32)P in the “conservative progeny” is 10 to 40% of that in the parental, showing that at least some of the (32)P in this area belongs to phages with parental DNA as the sole DNA component inside an unlabeled capsid, i.e., parental DNA which has been injected into the host and matured in a new capsid without replication or recombination. This phenomenon occurs to about the same extent in both single and multiple infection.